Oxford Handbook of Clinical Surgery, 3rd Edition - McLatchie, Greg, Borley, Neil; Chikwe, Joanna (OXFORD UNIVERSITY PRESS, 2007)
This, the third edition of the Oxford Handbook of Clinical Surgery, reflects the changes which have occurred in general surgery over the seventeen years since the first edition was published. Firstly, we have recruited the services of two new editors, a stark contrast to the original which was written by a single author with the assistance of a Surgical Registrar. Secondly, each chapter has been written by a Specialist Consultant or Registrar in the subject and, therefore, presents a modern, state-of-the-art treatise on each topic. Again, each condition is covered in the original two-page format with blank pages for accompanying notes. I am particularly grateful for the commitment that Jo Chikwe and Neil Borley have made, and also wish to thank staff at Oxford University Press for their support and patience. I am also grateful for the contribution and support given by many colleagues, and wish particularly to thank Anneli Thornton for her diligent preparation of the manuscript